2014
DOI: 10.1186/1471-2261-14-179
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors of ST-segment elevation myocardial infarction in young patients

Abstract: BackgroundAcute myocardial infarction (AMI) is often present in old populations and rare in young people. Its incidence significantly increased recent years. The mechanism and disease course of AMI in young people are probably different from that in old population. The aim of this study was to analyze clinical risk factors of STEMI in young patients.MethodsData was collected from consecutive patients ≤ 44 years of age (young; n = 86) and 60–74 years of age (old; n = 65) diagnosed with STEMI, and 79 young age-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
68
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 19 publications
13
68
2
7
Order By: Relevance
“…Yunyun et al [24] obtained similar results regarding the much higher prevalence of smoking among young patients with MI than among older patients. As many as 82.56% of individuals with MI aged ≤ 44 years and 41.54% of patients aged 60-74 years confirmed that they were smokers.…”
Section: Risk Factors For Myocardial Infarctionsupporting
confidence: 68%
See 3 more Smart Citations
“…Yunyun et al [24] obtained similar results regarding the much higher prevalence of smoking among young patients with MI than among older patients. As many as 82.56% of individuals with MI aged ≤ 44 years and 41.54% of patients aged 60-74 years confirmed that they were smokers.…”
Section: Risk Factors For Myocardial Infarctionsupporting
confidence: 68%
“…Pineda et al [23] reported hypertension in 28.5% of patients aged ≤ 45 years and in 49.5% of patients aged > 45 years with MI. A similar dependency, but with a higher prevalence of hypertension in both age groups, was observed by Yunyun et al [24]. Hypertension was present in 47.7% of young patients with MI and in 53.9% of older patients.…”
Section: Risk Factors For Myocardial Infarctionsupporting
confidence: 57%
See 2 more Smart Citations
“…Recently, it had been reported that the AMI) is a frequent cause of death or severe permanent disability, and the age of AMI patients is becoming increasingly young [12,13]. Thus, the present study was designed to investigate the possible pathogenic mechanism of AMI in patients younger than 60 years related to coagulation factors and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%